Analytical study of urban networks at the level of spatial development "Greater Damascus Region as case study" - عماد المصري; ماريا طعمه (Tishreen University, 2019)
مع زيادة الاهتمام بالتخطيط الإقليمي والمكاني في العالم وضرورة الاهتمام بأساليب التنمية المكانية الحديثة، زاد التفكير بضرورة الشبكات الحضرية كآلية لتحقيق التنمية المكانية في المدن المتوسطة والصغيرة التي تعمل بمفردها، من خلال تغيير الهيكل المكاني للإقليم ورفع مستوى الاستخدام النوعي والكمي له، وما يترتب عليه من علاقات لتجميع أصول وموارد مدن الإقليم والتي تقبل المشاركة في الفرص والمخاطر المحتملة.تم تطبيق الدراسة التحليلية باقتراح شبكة حضرية في إقليم دمشق الكبرى تدرس العقد والوصلات، واستخدام نظام التحليل SWOT لبحث الفرص والإمكانيات وعلاقتها بالإشكاليات والمحددات لاختيار السيناريو الأفضل للشبكة الحضرية يدرس مدى تأثير تطبيق مفهوم الشبكة الحضرية على تغيير الهيكل المكاني لإقليم دمشق الكبرى، كما تقترح آلية عمل قابلة للتنفيذ على المستوى المكاني-القطاعي. ويتوصل البحث في نهايته إلى مجموعة من النتائج والتوصيات، تحدد أهمية الربط الشبكي للمدن حسب موقعها، قادرة على التكيف مع التغيرات الحاصلة لمدننا السورية في ظل عدم وجود رؤية مستقبلية للتنمية الإقليمية تتلاءم مع الوضع الراهن، تراعي التغيرات الاقتصادية والاجتماعية والمكانية الحاصلة والتي تعيق تحقيق الإطار الوطني للتخطيط الإقليمي المقترح في عام 2010. With increased attention to regional and spatial planning in the world and the need to pay attention to modern spatial development methods, increased thinking for necessity urban networks as a mechanism for achieving spatial development in small and medium-sized cities, operating alone, has been enhanced by changing the spatial structure of the Territory, raising qualitative and quantitative use, To collect the assets and resources of the cities of the Region that accept participation in potential opportunities and risks. The analytical study was implemented by proposing an urban network in the Greater Damascus Region that examines the nodes and links, and uses the SWOT system to examine opportunities and possibilities, its relationship to the problems and determinants of selecting the best scenario for the proposed urban network examines the effect of applying the urban network concept on changing the spatial structure of the Greater Damascus Region, and propose a workable mechanism at the spatial-sectorial level. The research concludes with a set of conclusions and recommendations that determine the importance of the networking of cities according to their location, which is capable of adapting to the changes taking place in our Syrian cities. In the absence of a future vision for regional development that is appropriate to the current situation, taking into account the economic, social and spatial changes taking place; and which hinder the achievement of the proposed national framework for regional planning in 2010.